Heat transfer analysis of steady laminar 2D flow of CNTs-blood-based nanofluid over a moving permeable plate with viscous dissipation and thermal radiation - Rehman, Ali; Khan, Israr Ali; Salleh, Zabidin; İnç, Mustafa (Scientific Scholar Llc, 2025)
The properties of heat transmission in a continuous laminar 2D flow of a blood-based nanofluid (BBN) containing carbon nanotubes (CNTs) across a movable permeable surface were investigated in this study. It considers the effects of thermal radiation (TR) and viscous dissipation. The governing equations for heat transfer and fluid flow were employed to represent the BBN containing CNTs as nanoparticles. The fluid motion and temperature distribution are elucidated by utilizing the Navier-Stokes equations alongside the energy equation. The analysis includes the effects of TR, which explains the radiative heat exchange between the fluid and its surroundings, and viscous dissipation, which results from the fluid's internal conversion of mechanical energy into heat. The governing equations undergo simplification through the application of the boundary layer (BL) technique, yielding a set of nonlinear ordinary differential equations (ODEs). These resulting equations are subsequently solved using a semi-numerical technique called the homotopy analysis method (HAM). A detailed analysis was conducted on the impacts of various parameters, including the nanoparticle volume fraction, power law index, suction, TR parameter, couple stress parameter (CSP), injection parameter, and Eckert number (EN), on the Nusselt number (NN), velocity (VP), and temperature profile (TP). The velocity field is decreasing with the increase in nanoparticle volume friction and CSP, and increasing with the increase in the suction parameter. Similarly, the temperature field is increasing with an increase in the EN and TR parameters. The results of this investigation offer a significant understanding of the behavior of BBNs in heat transfer and may find use in thermal management systems and biomedical engineering. Also, the results provide helpful tips for optimizing biomedical cooling devices and targeted drug delivery systems where precise control of thermal and solute transport is critical
Keywords: Fluid dynamics; HAM; Mathematical modelling; MWCNT; Permeable surface; SWCNT